Caring for a relative with dementia: family caregiver burden - Kalokerinou, Athena; Papacostas, Savvas S.; Tsangari, Haritini; Sourtzi, Panayota A.; Papastavrou, Evridiki (My University, 2007)
Aim. This paper is a report of part of a study to investigate the burden experienced by families giving care to a relative with dementia, the consequences of care for the mental health of the primary caregiver and the strategies families use to cope with the care giving stressors. Background. The cost of caring for people with dementia is enormous, both monetary and psychological. Partners, relatives and friends who take care of patients experience emotional, physical and financial stress, and care giving demands are central to decisions on patient institutionalization. Method. A volunteer sample of 172 caregiver/care recipient dyads participated in the study in Cyprus in 2004–2005. All patients were suffering from probable Alzheimer’s type dementia and were recruited from neurology clinics. Data were collected using the Memory and Behaviour Problem Checklist, Burden Interview, Center for Epidemiological Studies-Depression scale and Ways of Coping Questionnaire. Findings. The results showed that 68Æ02% of caregivers were highly burdened and 65% exhibited depressive symptoms. Burden was related to patient psychopathology and caregiver sex, income and level of education. There was no statistically significant difference in level of burden or depression when patients lived in the community or in institutions. High scores in the burden scale were associated with use of emotional- focused coping strategies, while less burdened relatives used more problemsolving approaches to care-giving demands. Conclusion. Caregivers, especially women, need individualized, specific training in how to understand and manage the behaviour of relatives with dementia and how to cope with their own feelings.
Keywords: Caregiver burden; Coping; Dementia; Empirical research report; Family carers